Exploring Nursing Technicians’ Perceptions of Their Role in Delivering Holistic Patient Care and the Challenges of Implementing a Patient-Centered Care Approach in Saudi Arabia - Hana Saleh BqeelAlshamiri; Watfaa Khalef Albanagi; Noor Khalaf Mutlaq Aljameeli; Amal Furaih Alshammari; Monefa Fuoreh Saud Alshamry; Hana Meteb Alenzy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Nursing technicians play a vital role in delivering direct patient care and supporting the nursing workforce in healthcare settings in Saudi Arabia. However, their perceptions of their role in providing holistic, patient-centered care and the challenges they face in implementing this approach have not been extensively studied. This qualitative study aims to explore nursing technicians’ perceptions of their role in delivering holistic patient care and the challenges they encounter when implementing a patient-centered care approach in the Saudi Arabian healthcare context. Semi-structured interviews were conducted with 20 nursing technicians working in various healthcare settings in Saudi Arabia. Thematic analysis was used to identify key themes and subthemes related to nursing technicians’ perceptions and experiences. The findings revealed that nursing technicians perceived their role as essential in providing holistic patient care, with a focus on attending to patients’ physical, emotional, and spiritual needs. However, they also identified several challenges in implementing patient-centered care, including language barriers, cultural differences, workload pressures, and a lack of training and support. The study highlights the need for targeted interventions to support nursing technicians in delivering patient-centered care and to address the unique challenges they face in the Saudi Arabian healthcare context. Recommendations for practice, policy, and future research are discussed.